(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Acute lymphoblastic leukaemia (ALL) is a common malignancy in children which may cause significant nutritional problem as well as micronutrient deficiency like zinc. These deficiencies ultimately affect the outcome of the patient. Objective: The present study was done to identify the relationship of height, weight and serum zinc with acute lymphocytic leukemia in pediatric patients. Methods: This observational study was carried out in the Department of Pediatric Haematology and Oncology, Dhaka Medical College Hospital, Dhaka over a period of one year from July 2013 to June 2014. All children ranging from 1-10 years with newly diagnosed acute lymphocytic leukaemia were enrolled as case. An equal number of healthy children of similar age and sex were also included as control. The outcome measures were weight for height (wasting) and height for age (stunting) in children 5 or below 5 years of age and BMI in children > 5 years of age. The serum zinc level was also studied as a measure of micronutrient status. Result: Majority (80%) of the cases and 60% of the controls were 5 or < 5 years old. The mean ages of the children of cases and controls were almost similar (4.2 ± 2.3 vs. 4.8 ± 1.8 years, p >0.05). The groups were significantly different in terms of sex with male children being more prone to develop leukaemia than the females (p <0.05). Anaemia was invariably present. Majority (83.3%) of the children in the case group was wasted (weight for height Z-score lie below -2SD) as opposed 22.2% in the control group (p < 0.001). About 37% the children in the case group were stunted (height for age Z-score lies -2SD) as opposed to 16.7% in the control group (p< 0.05). The mean BMI was significantly lower in the case group than that in the control group (8.8 ± 2.7 vs. 17.1 ± 1.8, p < 0.001). Serum zinc level was also significantly lower in the former group than that in the latter group (0.7 ± 0.1 vs. 1.5 ± 0.5 mg/dl, p< 0.05). Conclusion: A good number leukaemia patients present with wasting and stunting and low BMI. Serum zinc level is significantly reduced which, in turn, may hamper various enzymatic functions in the body thereby reducing growth. Bangladesh J Child Health 2016; VOL 40 (1) :12-16